Current state and tendencies of developing library-information services in the Republic of Cameroon - J. .. Zemengue; T. .. Mbila (Библиосфера, 2017)
The article reflects the state of affairs in the field, which generalizes an operational experience of libraries in the Republic of Cameroon and foreign countries. The authors pay attention to the factors influencing the development of library-information services by proposing and suggesting solutions to develop this situation. The authors consider the library structure in the country, their various divisions and the personnel number using statistical tools; characterize the structure of library collections on their languages; examine in detail the most effective methods of serving users. The article managers the problems related to acquisition of libraries, stocks regulations and redistribution. The problem of insufficient training and retraining of library specialists in the library profession is brought up. Authors draw attention to unsatisfactory development of the material-technical base in Cameroon libraries, which is a consequence of the meager appropriations. The energy crisis in the country does not permit stable Internet connection. The necessity of creating portals and web-sites for libraries in the Republic of Cameroon was noted. Sufficient causes that have a direct impact on the quality of library information services for users are outlined. Authors propose a system for structuring the library system and indicate developing priorities of library-information services of the Republic of Cameroon. The article gives a comparative analysis of libraries’ activity in different countries. The authors conclude that there is no complete system of library-information servicing, flexible mechanisms and their interrelation. The country has no a single information space based on modern technology, reading rooms of major libraries fail to meet the growing demand for information services. Based on this study, the paper shows that there is need to create a unified platform for the Republic of Cameroon; identifies problems and different forms of developing the library-information service. The authors propose to pay more attention to modern remote non-stationary forms of library service delivery to the population as the most promising direction.